Penerapan Model Contextual Teaching and Learning (CTL) terhadap Pemahaman Konsep Ilmu Pengetahuan Alam (IPA) pada Siswa Kelas IV SDN 28 Kelakik - Selvia Dewi; Nurul Apsari; Novika Lestari (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2021)
Abstract: The purpose of this research was diagnotic students understanding of the science concept. This study was aimed at determining the differences in understanding the concept of science before and after applying the Contextual Teaching and Learning (CTL) model to students of elementary of SDN 28 Kelakik.The research design is an experimental study using the design of one group pretest and posttest. The data collection technique used is a test. The instruments used is the pretest and posttest test for understanding of concepts of science. The data analysis using one sample hypothesis testing (T-test). The study results implementation of Contextual Teaching and Learning (CTL) model in the learning of science obtained cognitive abilities result understanding students concepts pretes given treatment  was found still many students have low cognitive abilities and posttest given treatment found students with high cognitive abilities. (thitung = 39,70 ttabel = 1,71). So, there is the average concept understanding is higher than the Minimum Completeness Criteria after posttest applying the Contextual Teaching and Learning (CTL) model.Keywords: Concept of understanding, contextual teaching and learning (CTL) model, natural sciencesAbstrak: Penelitian ini bertujuan untuk mengetahui perbedaan pemahaman konsep Ilmu Pengetahuan Alam (IPA) sebelum dan sesudah menerapkan model Contextual Teaching and Learning (CTL) pada siswa kelas IV SDN 28 Kelakik. Jenis penelitian ini adalah penelitian eksperimen dengan menggunakan one group pretest posttest design. Teknik pengumpulan data yang digunakan adalah tes. Instrumen yang digunakan yaitu lembar soal pretest dan posttest untuk mengetahui pemahaman konsep IPA. Teknik analisis data menggunakan uji hipotesis (uji t) satu sampel. Hasil penelitian dengan menerapkan model Contextual Teaching and Learning (CTL) dalam pembelajaran IPA diperoleh hasil kemampuan kognitif pemahaman konsep siswa sebelum (pretest) diberi perlakuan ditemukan masih banyak siswa yang tingkat kemampuan kognitifnya rendah dan setelah (posttest) diberi perlakuan ditemukan siswa yang tingkat kemampuan kognitifnya tinggi. (t-hitung = 39,70 t-tabel = 1,71). Jadi, terdapat rata-rata pemahaman konsep lebih tinggi dari pada Kriteria Ketuntasan Minimal (KKM) sesudah  (posttest) menerapkan model Contextual Teaching and Learning (CTL).Kata-kata kunci: Pemahaman konsep, model contextual teaching and learning (CTL), IPA